UNRAVELING INDONESIA'S PEATLAND POLICIES: IMPLICATIONS AND INCONSISTENCIES - M, Mohd. Yusuf Daeng; Yusuf, Fadly Daeng; Yuliani, Febri; Zulkarnaini, Zulkarnaini (Universitas Syiah Kuala, 2024)
This article offers a legal perspective on the intricate web of Indonesian peatland policies, emphasizing their repercussions and inherent contradictions. Through an in-depth analysis of the legal frameworks and regulations governing peatland management in Indonesia, this study unravels the complexities and discrepancies present within these policies. It critically examines the repercussions stemming from these policies, shedding light on their unintended outcomes, including environmental, social, and economic ramifications. To address the complexities surrounding peatland policy in Indonesia, this article employes a multi-faceted legal research methodology. Primarily, it involves a doctrinal analysis, where relevant laws, regulations, and policies are systematically reviewed to identify inconsistencies and gaps. This study highlights the legal intricacies and challenges faced in implementing and enforcing peatland policy, ultimately seeking to propose a pathway for a more coherent, effective and harmonious legal framework to address the complexities of peatland management in Indonesia.